2010
DOI: 10.1108/02644401011008531
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and probabilistic failure prediction of grafts for aortic aneurysm

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…We plan to study this using FSI methods which have been used in our laboratory to simulate the onset of stent-graft migration and type I endoleak. 21 Our laboratory is also currently using physical experiments of PEAP in a mock flow loop to study its performance under more physiological hemodynamic conditions. One of our long-term goals is to optimize the mechanical properties and geometry of PEAP materials such that type I endoleak and migration are minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We plan to study this using FSI methods which have been used in our laboratory to simulate the onset of stent-graft migration and type I endoleak. 21 Our laboratory is also currently using physical experiments of PEAP in a mock flow loop to study its performance under more physiological hemodynamic conditions. One of our long-term goals is to optimize the mechanical properties and geometry of PEAP materials such that type I endoleak and migration are minimized.…”
Section: Discussionmentioning
confidence: 99%
“…1,17 Both PCL and PU are blood compatible and have been investigated for cardiovascular devices. 1,19,21,29 Testing in our laboratory revealed that PCL/PU blends are thermoformable at 55°C, resistant to biodegradation, and have mechanical properties that can be controlled by varying PCL/ PU ratios. 3 In order for PEAP to prevent AAA rupture and provide a viable option to treat AAA, it must reduce aneurysm wall stress at least as effectively as stentgrafts.…”
Section: Introductionmentioning
confidence: 99%
“…It can handle problems with discontinuous or binary responses [8,13,20]. In addition, the approach can easily handle multiple constraints [15,21].…”
Section: A Explicit Design Space Decomposition (Edsd)mentioning
confidence: 99%
“…These however require the precise modeling of the mechanical properties of the implant in order to optimize its functions in-vivo. it is difficult to deterministically quantify design outcome invivo due to variation in environmental and stress conditions, Computer Aided Deisgn (CAD) of mainly orthopedic implants have employed probabilistic approaches ranging from wear models to finite element simulations for evaluation and optimization (Layman et al, 2010;Kayabasi and Ekici 2008;Laz and Browne 2010;Pal et al, 2008;Chevalier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%